(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
This study was conducted to introduce herd health programme to reduce the economic loss of local chickens and increase the income of poor households in Gizawa community of Dutsinma Local Government of Katsina State. A purposive and stratified sample method was used in selecting 16 local poultry farmers in the study area. Biosecurity measure was introduced with disinfectant (7% Tar Acid Phenol and 2% crysylic creosote). It was used to fumigate all stagnant and flowing sewage water. The result of the study revealed that biosecurity measure is effective method used to reduce/limit the rate of mortality and economic loss of local poultry farmers due to Newcastle disease. There was reduction in mortality and improve productivity thereby increasing farmers income. Biosecurity measure has been a method of preventing Newcastle disease, thus can be recommended to public and private extension agent to advocate or amplify the use of biosecurity measures in the prevention of Newcastle disease.